2007
DOI: 10.1515/bc.2008.008
|View full text |Cite
|
Sign up to set email alerts
|

Collagen IV regulates Caco-2 cell spreading and p130Cas phosphorylation by FAK-dependent and FAK-independent pathways

Abstract: We previously observed that collagen IV regulates Caco-2 intestinal epithelial cell spreading and migration via Src-dependent p130 Cas phosphorylation and stimulates focal adhesion kinase (FAK). However, the role of FAK and the related kinase, Pyk2, in Caco-2 spreading and migration is unclear. FAK-or Pyk2-specific siRNAs reduced protein levels by 90%. However, when detached cells were replated on collagen IV neither individual nor combined FAK and Pyk2 siRNAs affected the cell spreading rate. As combined FAK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 43 publications
1
15
0
1
Order By: Relevance
“…In addition to the present findings, others have reported that both FAK and SFKs are crucial for CasSD phosphorylation (Fonseca et al, 2004;Hamamura et al, 2008;Sanders and Basson, 2008). Results from an earlier study of FAK mutants indicate that the ability of overexpressed FAK to enhance CasSD phosphorylation relies on the autophosphorylation of FAK residue Y397 (Ruest et al, 2001).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In addition to the present findings, others have reported that both FAK and SFKs are crucial for CasSD phosphorylation (Fonseca et al, 2004;Hamamura et al, 2008;Sanders and Basson, 2008). Results from an earlier study of FAK mutants indicate that the ability of overexpressed FAK to enhance CasSD phosphorylation relies on the autophosphorylation of FAK residue Y397 (Ruest et al, 2001).…”
Section: Discussionsupporting
confidence: 79%
“…Cas and FAK complex formation is important for CasSD phosphorylation FAK is a crucial binding partner of Cas and is responsible for phosphorylation of CasSD (Fonseca et al, 2004;Sanders and Basson, 2008). FAK and Cas coimmunoprecipitated with each other in adherent fibroblasts and fibroblasts in suspension (Fig.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been reported that collagen can promote cell survival in vitro by inhibition of apoptosis, via a β1 integrin-dependent mechanism [72]. In addition, collagen participates in cell spreading through p130 Cas phosphorylation via FAK-dependent and FAK-independent integrin receptor pathways [73]. Collagen is also implicated in the induction of proliferation via FAK activation and downstream signaling pathways (Src, MEK, PI3-kinase, and p38 MAPK) [70, 74] (Figure 1).…”
Section: Ecm-cell Interactions In Homeostatic Myocardiummentioning
confidence: 99%
“…In addition, collagen participates in cell spreading through p130Cas phosphorylation via FAK-dependent and FAK-independent integrin receptor pathways [9,10]. Finally, collagen plays a key role in cell migration through the activation of FAK and PI3-K, leading to elevated Rac1 activity as a downstream consequence in activated cell migration [11].…”
Section: Introductionmentioning
confidence: 99%